2015
DOI: 10.1002/cmdc.201500360
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and Biological Studies of Sesquiterpene Polygodial: Activity of 9‐Epipolygodial against Drug‐Resistant Cancer Cells

Abstract: Polygodial, a terpenenoid dialdehyde isolated from Polygonum hydropiper L., is a known TRPV1 agonist. In this investigation a series of polygodial analogues were prepared and investigated for TRPV1 agonistic and anticancer activities. These experiments led to the identification of 9-epipolygodial, possessing antiproliferative potency significantly exceeding that of polygodial. Epipolygodial maintained potency against apoptosis-resistant cancer cells as well as those displaying the MDR phenotype. In addition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 79 publications
1
31
0
Order By: Relevance
“…Unfortunately, the manner in which polygodial inhibits TRPV1 and whether covalent pyrrole adducts are involved remains to be elucidated. 32 …”
Section: Paal–knorr Modifications Of Biological Targets With Naturamentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the manner in which polygodial inhibits TRPV1 and whether covalent pyrrole adducts are involved remains to be elucidated. 32 …”
Section: Paal–knorr Modifications Of Biological Targets With Naturamentioning
confidence: 99%
“…32,33 To obtain firm evidence of Paal–Knorr reactivity in these compounds, we attempted to isolate such pyrrole adducts (Scheme 9). Our proposed explanation for the lack of stability of the produced pyrroles was their electron-rich character and, thus, high propensity toward oxidation.…”
Section: Paal–knorr Modifications Of Biological Targets With Naturamentioning
confidence: 99%
See 1 more Smart Citation
“…In our own attempts [55] to demonstrate the feasibility of what could be referred to as the modified Paal-Knorr [56] pyrrolylation of proteins by 1 , it was found that although N -alkyl pyrrole 2 (R = Bn, Figure 2A) formed, it was extremely unstable and readily oxidized in air. This stability problem was solved by the preparation and successful isolation of electron-deficient N -aryl pyrroles 2 (R = Ph and p -NO 2 -C 6 H 4 ); however, these adducts are obviously not relevant biologically as the resultant covalent complex with a lysine residue would be an alkyl pyrrole and thus also readily oxidizable.…”
Section: Chemistrymentioning
confidence: 99%
“…Encouraged by several earlier reports of cytotoxic activity associated with 1 [4954], we prepared a series of its chemical derivatives and studied their TRPV1 agonistic and anticancer activities in detail. A related publication resulting from this study describes the discovery of useful anticancer activities associated with 9-epipolygodial [55]. Herein, we present a series of C12-Wittig derivatives of 1 that exert their antiproliferative action mainly through cytostatic effects and possess promising activities against cancer cells resistant to apoptosis as well as those with an MDR phenotype.…”
Section: Introductionmentioning
confidence: 99%